Romeo and Juliet - Shakespeare, William, 1564-1616 (Shakespeare, William, 1564-1616. Works. 1982., 2008)
This edition of Shakespeare's 'Romeo and Juliet' offers modernized texts of both the 1599 good quarto and the short, or bad quarto of 1597, regarding each as an independent witness to a mobile text which changed in composition as Shakespeare wrote it.